Menelisik Kualitas dan Pemahaman Hadis tentang Faktor yang Mendorong Rasulullah SAW Menikahi Aisyah - Riri Fitria; Erizal Ilyas (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2022)
The marriage practice of Prophet Muhammad (SAW) with Aisha RA has generated various perspectives among Islamic law experts. Starting from Aisha RA's young age, which is considered too young, and the figure of Prophet Muhammad who is made as a role model by Muslims. This research will attempt to find the quality as well as the understanding of hadiths about the factors that led to the marriage. This is important to refute some views that claim that Prophet Muhammad deliberately married an underage child and even took away Aisha RA's childhood. Likewise, the view that Prophet Muhammad tended to marry underage girls. The method used to study the quality of related hadiths is the method of Takhrij Al-Hadith. This is because the hadith that explains this was narrated by Imam Ahmad bin Hanbal, whose authenticity cannot be confirmed yet. As for finding the understanding of hadith scholars about the hadith, the method of understanding the hadith is used so that the comprehension can be known comprehensively. Of the two hadiths that tell about the factors of Aisha RA's marriage to Prophet Muhammad, it was found to be of high quality (shahih), so it can be concluded that the marriage was driven by the command of revelation and the initiative of his companion named Khawlah. This finding refutes the biased view of some people regarding the marriage of Prophet Muhammad with a young girl and even